2018
DOI: 10.1002/sia.6403
|View full text |Cite
|
Sign up to set email alerts
|

Damage accumulation and structural modification in a‐ and c‐plane GaN implanted with 400‐keV and 5‐MeV Au+ ions

Abstract: c‐plane (0001) and a‐plane (11‐20) gallium nitride (GaN) epitaxial layers were grown by Metal organic Vapour Phase epitaxy (MOVPE) on sapphire and subsequently implanted with 400‐keV and 5‐MeV Au+ ions using fluences 5 × 1014 to 5 × 1015 cm−2. The shallow Au depth profiling was accomplished by Rutherford backscattering spectrometry. The structural changes during implantation and subsequent annealing were characterised by Rutherford backscattering spectrometry channelling and Raman spectroscopy. The interplay b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Raman spectroscopy follows the longitudinal and transverse vibrations of Zn and O‐sublattices, which could be influenced by heavy dopant incorporation and oxygen rearrangement. Concerning the right‐hand shoulder at the E 2 low phonon (see Figure 2), similar results were obtained in Li et al 21 where the authors observed a low‐frequency shoulder at the E 2 low phonon caused by the substitutional disorder, whose intensity increased with increasing Ag concentration in the ZnO lattice; this effect could also be presumed for Au ions, however it was shown that Au is not entering subsitutional positions in wurtzite structure to the higher extent 22. Thus this phenomenon is more likely connected to selection rules relaxation.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Raman spectroscopy follows the longitudinal and transverse vibrations of Zn and O‐sublattices, which could be influenced by heavy dopant incorporation and oxygen rearrangement. Concerning the right‐hand shoulder at the E 2 low phonon (see Figure 2), similar results were obtained in Li et al 21 where the authors observed a low‐frequency shoulder at the E 2 low phonon caused by the substitutional disorder, whose intensity increased with increasing Ag concentration in the ZnO lattice; this effect could also be presumed for Au ions, however it was shown that Au is not entering subsitutional positions in wurtzite structure to the higher extent 22. Thus this phenomenon is more likely connected to selection rules relaxation.…”
Section: Resultssupporting
confidence: 85%
“…Thermally more stable and persistent damage was also observed in the past in a ‐plane GaN after annealing in N 2. 20,22 Oxygen rearrangement after annealing has been confirmed with Raman spectroscopy in all ZnO orientations; it could be connected to DLE reduction and a shift to higher wavelengths.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…For higher fluences the formation of extended defects such as stacking faults and dislocation loops sets in [25]. Furthermore, for the highest fluence the RDL is considerably higher in c-GaN than in a-GaN, a fact that has been previously seen for Ar implantation at low temperature [25] as well as for rare earth implantation at room temperature [33,34]. Figure 1 -Relative defect level profiles derived from the RBS/C spectra using a two-beam model for both planar orientations.…”
Section: Resultsmentioning
confidence: 59%